2016
DOI: 10.1159/000452603
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment and Structural Neuroimaging Abnormalities Among Patients with Chronic Kidney Disease

Abstract: Background/Aims: Cognitive impairment and abnormal structural neuroimaging is common in chronic kidney disease patients. We aimed to explore its association with dialysis modality and the relationship between cognitive impairment and abnormal structural neuroimaging. Methods: Sixty peritoneal dialysis patients and 30 hemodialysis and 30 non-dialyzed stage 3-5 chronic kidney disease patients without history of stroke were enrolled for the study. Participants were matched for age, gender, education, diabetes sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 35 publications
1
26
0
2
Order By: Relevance
“…The third objective was to analyze associations between EF performance and clinical and biochemical variables [27]. Decision-making performance (IGT) was positively associated with the total number of months previously transplanted.…”
Section: Discussionmentioning
confidence: 99%
“…The third objective was to analyze associations between EF performance and clinical and biochemical variables [27]. Decision-making performance (IGT) was positively associated with the total number of months previously transplanted.…”
Section: Discussionmentioning
confidence: 99%
“…Injury to the brain can be assessed either by radiological methods, which provide largely structural information, or validated neurocognitive tests, which provide (arguably more important) functional information . Some but not all observational studies have suggested that patients who undergo maintenance peritoneal rather than hemodialysis have a slower decline in cognitive function, or fewer abnormalities on brain magnetic resonance imaging (MRI) . Increasing hemodialysis vintage has been associated with reductions in baseline cerebral blood flow, frontal lobe oxygenation and cognitive performance, as well as a greater burden of white matter abnormalities on MRI, particularly subtle changes on diffuser tensor imaging (DTI) .…”
mentioning
confidence: 99%
“…18 Some but not all observational studies have suggested that patients who undergo maintenance peritoneal rather than hemodialysis have a slower decline in cognitive function, or fewer abnormalities on brain magnetic resonance imaging (MRI). 19,20 Increasing hemodialysis vintage has been associated with reductions in baseline cerebral blood flow, frontal lobe oxygenation and cognitive performance, as well as a greater burden of white matter abnormalities on MRI, particularly subtle changes on diffuser tensor imaging (DTI). [21][22][23] The potential for confounding in these studies is considerable, not least by time and treatment indication.…”
mentioning
confidence: 99%
“…Neuroimaging has been established as a reliable tool for assessing the neuropathologic mechanisms of cognitive impairment in ESRD patients [13,14]. Resting-state functional magnetic resonance imaging (rs-fMRI) showed that ESRD patients have lower ALFF values and abnormal brain functional connectivity in default mode network (DMN) regions when compared with healthy controls [15].…”
Section: Introductionmentioning
confidence: 99%